Miscanthus litter additions induce a successional change in the soil micro-food web with apparent decreases in soil nitrogen - Krisztina Mosdossy; Cynthia M. Kallenbach; Jacynthe Masse; Benjamin Mimee (Soil Biology and Biochemistry, 2024)

Prevalence of Verticillium spp. and Pratylenchus spp. in Commercial Potato Fields in Atlantic Canada - Dahu Chen; Ryan Barrett; Benjamin Mimee; Tanya Arseneault; Louis-Pierre Comeau; Kamrun Nahar; Sebastian Ibarra Jimenez; Bernie J. Zebarth (American Journal of Potato Research, 2024)
A survey of New Brunswick (NB) and Prince Edward Island (PEI) potato fields in crop rotation phase prior to potato production was conducted in fall (October and November) between 2017 and 2021. A total of 113 and 126 fields for NB and PEI, respectively, were surveyed with 20 to 35 fields each year tested in each province. Root lesion nematodes (RLN, Pratylenchus spp.) were detected in 99 and 98% of the fields for NB and PEI, respectively, and two root lesion nematode species, P. crenatus and P. penetrans , were identified in both provinces from 2017 to 2021. Based on 2019 and 2020 results, all surveyed fields in NB and PEI were detected with P. crenatus , while only 29 and 43% of the fields in NB and PEI were detected with P. penetrans , respectively. P. crenatus accounted for 96 and 89% of the populations for NB and PEI, respectively, while P. penetrans accounted for 4 and 11% in commercial fields, respectively. In a single in-depth sampled experimental field with a history of severe potato early dying complex in 2018 in NB, P. crenatus accounted for 88% and P. penetrans was 12%. Verticillium dahliae was detected in 94 and 92% of potato fields in NB and PEI, respectively. All isolates obtained from potato cv. “Russet Burbank” in a baiting trial were V. dahliae , belonging to two lineages. V. albo-atrum was detected in a few fields at very low level, except two fields in NB where V. albo-atrum was predominating over V. dahliae . Rotation crops did not affect V. dahliae population densities for NB and PEI, and did not affect RLN population in NB, but significantly affected RLN in PEI. Fall green cover crop did not affect the populations of RLN and V. dahliae in PEI. The present study revealed that the potato pathogenic root lesion nematode P. penetrans was present in less than 50% of surveyed fields and accounted for around 10% of root lesion nematode population in NB and PEI, and V. dahliae was the dominant species and was present in greater than 90% of surveyed fields in both provinces.

Adding ligneous litter to cultivated organic soil changes the soil micro-food web and alters soil nitrogen availability - Krisztina Mosdossy; Cynthia M. Kallenbach; Benjamin Mimee (Applied Soil Ecology, 2024)